Peranan Guru Bk Untuk Meningkatkan Efektifitas Pembelajaran Siswa Melalui Layanan Informasi Di Mts. Yapi Bkai - Hilda Rahayu Daulay (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The type of research in writing is descriptive qualitative research. As for the informants in this study were principals, subject teachers, counseling teacher, and student. This data collection technique uses data colltection tools, namely observation, interviews, and documentation. While the analysis of the data from the result of this study was conducted based on descriptive analysis, the analysis consisted of three flow of analysis that interacted namely data reduction, data presentation, and conclusion drawing. The objectives of this study are : 1) To describe what role counseling teachers do to improve student learning effectiveness through information services at MTs. YAPI BKAI Sei Karang. 2). To find out how information service are implemented to improve student learning effectiveness through information services at MTs. YAPI BKAI Sei Karang. 3). To find out what are the inhibithing factors of counseling tutors to improve student learning effectiveness through information service at MTs YAPI BKAI Sei Karang. After the research was conducted, the results showed that the role of counseling services and still use the counseling teachers at MTs YAPI BKAI Sei Karang had not run effectively because there were no special counseling hours to conduct guidance and counseling service and still use the counseling method at empty hours. Then the implementation of information services at MTs. YAPI BKAI Sei Karang has also not been implemented properly and effectively because counseling tutors still provide information service in a classical manner which is like preparing service material about learning effectiveness. Then the inhibiting factor was the implementation of counseling at MTs. YAPI BKAI Sei Karang because there were more students in the school than those who were more students in the school than those who were supposed to be foster counselors and also inadequate facilities and infrastructure that support the counseling activities at MTs. YAPI BKAI Sei Karang